THE PERENNIALISM APPROACH IN THE DEVELOPMENT OF ISLAMIC RELIGIOUS EDUCATION CURRICULUM - Muhammad Herlambang; Tasman Hamami; Alfitra Firmansyah (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2024)
Islamic religious education in Indonesia has undergone various changes in the development of its curriculum. Education itself has an important and influential role in changing a person. In the context of the moral and moral crisis that is currently sweeping Indonesia, education is expected to help overcome the current crisis. Seeing these problems, the perennialism approach in the development of the Islamic religious education curriculum aims to maintain traditional values that are considered to have eternal and universal truths. In this approach, the curriculum is designed to focus on fundamental values such as faith, morals, and worship, as well as the formation of strong character and good morals. Effective and efficient teaching methods, such as discussion, question and answer, and problem solving, are also emphasized in this approach. It needs to be adapted to the conditions of the times so that traditional values remain relevant in modern life.